Some fundamental issues in the semantic analysis of prepositions1 - Guarddon Anelo, Carmen (Estudios Ingleses de la Universidad Complutense, 2005)
This first part of this paper offers an evaluation of several semantic analyses of prepositions. The interest of these lexical items resides in the fact that they are highly polysemous. Therefore, I focus on how the analyses considered treat the question of prepositional polysemy. In the second part of the paper, I demonstrate by highlighting different facts about the semantics of prepositions that monosemic accounts fail to expose the linguistic, if not cognitive, reality of prepositions. My purpose is to show that prepositions, being closed-class lexical items, manifest lexical intrinsic properties that are revealed at different levels of analysis. Thus, monosemic and polysemic approaches should be reconciled into a single account because they both help to shed some light on linguists’ major concern about the meaning of prepositions, which is their ability to categorise multiple situations within the physical realm and categorise in a variety of domains.